A beautiful new species of Dichorisandra (Commelinaceae) from the mountains of northeastern Goiás, Brazil - Silva, Marcos José Da; Aona, Lidyanne Yuriko Saleme (Phytotaxa, 2023)
Dichorisandra pulcherrima, a new species from the mountains of the northeastern state of Goiás, Brazil, is described and illustrated here. Its morphological relationships are discussed and compared with those of D. villosula, D. hexandra, and D. pubescens, especially with the first two, with which it is most similar. However, it differs from all of them by a combination of characters that includes the erect habit without pendulous branches, the presence and type of indumentum in the vegetative parts, stem diameter, internode length, the color, shape and size of the leaf blades, the size of the inflorescence, the shape and size of the cincinnus bracts, and the color and shape of the petals and pollen sacs.